THE EFFECT OF SLEEP AND RELAXATION BENSON ON IMPROVING THE QUALITY OF SLEEP AMONG HEART FAILURE PATIENTS: A LITERATURE REVIEW: DOI: https://doi.org/10.35654/ijnhs.v2i1.69 - Musaddad - Kamal (International Journal of Nursing and Health Services (IJNHS), 2019)
Abstract Heart failure has now become a global cardiovascular problem with high mortality and disability. Sleep disturbance is a common problem in heart failure patients. Sleep disorders that occur in patients with heart failure will cause increased levels of urine catecholamine, plasma leptin, and inflammatory markers. These changes are related to the development of hypertension, activation of the sympathetic nervous system, and blunting of chemoreflex, which will increase the heart burden and ultimately lead to a poor prognosis. Sleep disorders in heart failure patients can be treated with psychological interventions and behaviors including sleep hygiene and Benson relaxation. Nurses, as one of the health professionals, have an important role in this matter. This is because the scope of nursing is meeting basic human needs, namely sleep. Through intervention in sleep hygiene and relaxation, Benson is expected to be able to improve the patient's sleep quality. Keywords: benson relaxation, heart failure, sleep disorders, sleep hygiene.